NITROGEN UTILIZATION BY DAIRY GOATS OFFERED DIFFERENT NITROGEN SOURCES AS SUPPLEMENTS IN HIGH ISOCALORIC ENERGY CONCENTRATES - Asih, A.R.S.; Wiryawan, K.G.; Young, B.A. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
Twelve growing female goats (Anglo-Nubian) were assigned to a multiple latin square designexperiment to evaluate the effectiveness of additions of nitrogen (N) supplements to a high isocaloricenergy ration on N utilization. In this experiment, microbial synthesis and N balance were assessed. Thedaily rations were either unsupplemented barley meal (BM), or BM supplemented with one of threenitrogen sources. All rations were isocaloric (3.0 Mcal ME/kg DM) and the N supplements weresoybean meal (BSBM), cottonseed meal (BCSM) or urea (BU) to provide 2.9% N in the concentratecomponent. The unsupplemented BM contained 1.7% N. The addition of N supplements to the rationenhanced N utilization in dairy goats. The organic matter (OM) intake, N intake, N balance, andmicrobial N synthesis for BM, BSBM, BCSM and BU were 660.5 g, 721.9 g, 728.1g and 703.5 g; 13.5g, 21.5 g, 20.9 g and 20.7 g; 2.7 g; 7.1 g, 5.4 g, and 5.7 g; and 14.1 g 19.1 g, 19.1 g, and 20.0 g,respectively. It can be concluded that when sufficient dietary energy was available for ruminal microbialactivities, the source of N did not affect N balance, and microbial N synthesis.